2011
DOI: 10.4236/am.2011.27118
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Crank-Nicolson Scheme for Burgers’ Equation

Abstract: In this work we generate the numerical solutions of the Burgers' equation by applying the Crank-Nicolson method directly to the Burgers' equation, i.e., we do not use Hopf-Cole transformation to reduce Burgers' equation into the linear heat equation. Absolute error of the present method is compared to the absolute error of the two existing methods for two test problems. The method is also analyzed for a third test problem, numerical solutions as well as exact solutions for different values of viscosity are cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The method is proved to be consistent and is of order two in space and time. The numerical solution is calculated for two test problems with different values of constant of diffusivity k. It is observed that the method is more accurate than the existing numerical methods [9], [27], [31]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The method is proved to be consistent and is of order two in space and time. The numerical solution is calculated for two test problems with different values of constant of diffusivity k. It is observed that the method is more accurate than the existing numerical methods [9], [27], [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Numerical solutions of one dimensional nonlinear Burgers equation (1) are obtained by Crank-Nicolson Type method (4) for two problems given in section 1 and results are compared with existing three methods [9], [27], [31] and exact solution given in section 1. It is observed that the the method (4) gives more accurate solution than the other methods.…”
Section: Crank-nicolson Type Methodsmentioning
confidence: 99%
See 3 more Smart Citations